If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 = 3y Solving 21 = 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 21 + -3y = 3y + -3y Combine like terms: 3y + -3y = 0 21 + -3y = 0 Add '-21' to each side of the equation. 21 + -21 + -3y = 0 + -21 Combine like terms: 21 + -21 = 0 0 + -3y = 0 + -21 -3y = 0 + -21 Combine like terms: 0 + -21 = -21 -3y = -21 Divide each side by '-3'. y = 7 Simplifying y = 7
| 3(2s-3)=-(7-8) | | c=582/3 | | 20x^2-7x=0 | | 4r^3(2r^2)= | | 20z+80=180 | | -x=0.87 | | 6(y-5)=(10+3y) | | -3n^2-26n-48=0 | | -3(4p+2)-2(6-11p)=3(8+3p) | | -30y=9y^2+25 | | X^2y^2-49=o | | y=-5x^2-4x+1 | | 9v^2+25=-30v | | y=-5x^2+3x+10 | | -1-5(3-x)=2(x-2) | | d-9=-18 | | x-65=32 | | 3y^2+7y=6 | | y^2-y-2=0 | | 6X-(5X+6)=-4 | | 3(6z-1)-4(z+3)=3(z+1) | | 0(-19)= | | 3x+2=-5 | | 3(x+4)-6x=2(4-2x) | | -5y+12=67 | | -4(w-9)(-w+1)=0 | | -3y+9=-4y+6 | | x^2+13=8x | | -3x+7-2x=4x-6+8 | | (5z-9)(7+z)=0 | | 40+4y-12=12y-14-2y | | -3(2s-1)-3=-2(s+8)-2 |